A Developmental Analysis of Caregiving Modalities Across Infancy in 38 Low‐ and Middle‐Income Countries. Issue 5 (17th August 2015) - Bornstein, Marc H.; Putnick, Diane L.; Lansford, Jennifer E.; Deater‐Deckard, Kirby; Bradley, Robert H.
<x xml:space="preserve">Abstract</x> Caregiving is requisite to wholesome child development from the beginning of life. A cross‐sectional microgenetic analysis of six caregiving practices across the child's 1st year (0–12 months) in 42, 539 families from nationally representative samples in 38 low‐ and middle‐income countries is reported. Rates of caregiving varied tremendously within and across countries. However, caregiving practices followed one of two developmental trajectories: (a) greater proportions of caregivers read, told stories, and named, counted, and drew with each additional month of infant age, and (b) proportions of caregivers who played, sang songs, and took their infants outside increased each month from birth but reached an asymptote at 4–5 months. Rates and growth functions of caregiving have implications for infant care and development.